Type I Interferon Responses by HIV-1 Infection: Association with Disease Progression and Control - Soper, Andrew; Kimura, Izumi; Nagaoka, Shumpei; Konno, Yoriyuki; Yamamoto, Keisuke; Koyanagi, Yoshio; Sato, Kei (Frontiers in Immunology, 2018)
Human immunodeficiency virus type 1 (HIV-1) is the causative agent of acquired immunodeficiency syndrome (AIDS) and its infection leads to the onset of several disorders such as the depletion of peripheral CD4+ T cells and immune activation. HIV-1 is recognized by innate immune sensors that then trigger the production of type I interferons (IFN-Is). IFN-Is are well known cytokines eliciting broad anti-viral effects by inducing the expression of anti-viral genes called interferon-stimulated genes (ISGs). Extensive in vitro studies using cell culture systems have elucidated that certain ISGs such as APOBEC3G, tetherin, SAMHD1, MX2, GBP5 and SLFN11 exert robust anti-HIV-1 activity, suggesting that IFN-I responses triggered by HIV-1 infection are detrimental for viral replication and spread. However, recent studies using animal models have demonstrated that at both the acute and chronic phase of infection, the role of IFN-Is produced by HIV or SIV infection in viral replication, spread and pathogenesis, may not be that straightforward. In this review, we describe the pluses and minuses of HIV-1 infection stimulated IFN-I responses on viral replication and pathogenesis, and further discuss the possibility for therapeutic approaches.